LEADING BY DESIGN TO GREATER HEIGHTS - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
The recent outcomes of the Quacquarelli Symonds (QS) World University Rankings highlighted the fact that all the six indicators assessed have human factors imbued in them and this is the fact that is recognised by Universiti Sains Malaysia (USM).